PENGARUH FASILITAS KERJA TERHADAP PRODUKTIVITAS KANTOR DESA SEBERANG PEBENAAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Zulfaini; Donal Devi Amdanata (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The purpose of this research is to determine the influence of work facilities on productivity, thein fluence of work facilities on job satis faction, and thein fluence of work facilities on the productivity of village officials with job satisfaction as a mediator at Seberang Pebenaan Village Office. The population in this study consisted of employees and official sof Pebenaan Village Office, totaling 48 people. The sampling technique used non-probability sampling method (non-random sampling), namely Saturated Sampling Technique, which is a sampling technique that takes all members of the population as samples. The statistical method used is Structural Equation Model (SEM) to test the research hypotheses using SmartPLS 4 software. The results of the study show a significant influence of work facilities on productivity in Seberang Pebenaan Village Office officials, a significant influence of work facilities on job satisfaction in Seberang Pebenaan Village Office officials, and an influence of work facilities on productivity with job satisfaction as a mediating variable in Seberang Pebenaan Village Office officials.